Programming of control system for self-balancing scooter / Muhamad Yusuf Ibrahim. - Ibrahim, Muhamad Yusuf (2009)
The aim of this project is to develop and implement a suitable programming for the Self balancing Scooter by using PIC Microcontroller. The self-balancing scooter is a two wheeled self-balancing vehicle which is capable of carrying via the wheels underneath the riders of centre gravity. It involves the programming and. application of the control system to perform specific task. The programming will control the movement of the scooter. The program is developed by using PIC Microcontroller embedded in Custom Computer Services (CCS) PCWHD IDE Compiler software. The program will use the language of C-code. So, only certain command can be used in the language which than uses PIC Microcontroller as software to hardware interfacing.